SISTEM INFORMASI PENGOLAHAN DATA INDUSTRI KECIL MENENGAH (IKM) DI KOTA CILEGON - Ely Nuryani; Rustam Effendi; Waliadi Gunawan; Sandy Ruliandy (Journal of Innovation And Future Technology, 2025)
Small and Medium Industries (SMIs) are community-driven business sectors that have demonstrated significant contributions to economic development. They play a crucial role in providing alternative and productive economic activities. This study focuses on the Department of Industry and Trade of Cilegon City, which faces challenges in collecting data on SMIs across districts, compiling records of supervised enterprises, and monitoring their progress. The objective of this research is to design and develop a Management and Data Collection Application for SMIs in Cilegon City to enhance the efficiency of SMI development activities. The application was developed using the Rapid Application Development (RAD) methodology, aligned with the System Development Life Cycle (SDLC). The design process employed an Entity Relationship Diagram (ERD) and Unified Modeling Language (UML), specifically a Use Case Diagram. The system is web-based and implemented using the Code Igniter framework, PHP programming language, and a MySQL database.